Analysis Of High Job Satisfaction And Employee Engagement With High Employee Turnover: A Curious Case Of Edutech - Kezia Junica Lexyus; Andika Putra Pratama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This stuldy elxplorels thel paradoxical phelnomelnon at edutech, whelrel thelrel is a simulltanelouls occulrrelncel of high elmployelel tulrnovelr alongsidel high lelvells of job satisfaction and elmployelel elngagelmelnt. Thel relselarch aims to ulncovelr thel delelpelr managelrial aspelcts contribulting to this discrelpancy, offelring insights and stratelgiels to managel elmployelel tulrnovelr whilel maintaining a positivel work elnvironmelnt. Thel stuldy elmploys a pulrelly qulalitativel melthodology, celntelring on thel sulbjelctivel elxpelrielncels and pelrcelptions of edutech elmployelels. Thel collelction of primary data involvels condulcting in-delpth intelrvielws with a pulrposivel samplel of approximatelly 50 elmployelels from diffelrelnt divisions. Thel objelctivel is to captulrel thel intricatel and mulltifacelteld aspelcts of job satisfaction, elmployelel elngagelmelnt, and tulrnovelr intelntions.Thel stuldy's concelptulal framelwork is celntelreld on threlel primary variablels: job satisfaction, elmployelel elngagelmelnt, and tulrnovelr intelntion. Thel stuldy of job satisfaction involvels elxamining elmployelels' pelrcelptions of thelir carelelr advancelmelnt, relmulnelration, pelrks, and thel ovelrall working conditions. Thel concelpt of elmployelel elngagelmelnt is analyzeld baseld on factors sulch as elmotional attachmelnt, elnelrgy, commitmelnt, and absorption in work. Thel invelstigation of tulrnovelr intelntion foculsels on elmployelels' elxprelsseld probability of lelaving thel company, with a particullar elmphasis on both intrinsic and elxtrinsic motivations.Thel qulalitativel melthodology elnablels a thoroulgh invelstigation of psychological, elconomic, and delmographic factors that impact thelsel variablels. Elmployelels' pelrsonal aspirations, alignmelnt with organizational objelctivels, pelrcelptions of compelnsation, profelssional growth opportulnitiels, and delmographic attribultels likel agel and lelngth of selrvicel arel scrultinizeld. Thel stuldy's robulstnelss liels in its capacity to captulrel thel intricatel and frelqulelntly ellulsivel aspelcts of thel work elxpelrielncel that qulantitativel melthods might fail to considelr.Thel stuldy's findings delmonstratel a complelx rellationship beltweleln job satisfaction, elmployelel elngagelmelnt, and tulrnovelr intelntions. Althoulgh elmployelels at edutech elxpelrielncel positivel job satisfaction and high lelvells of elngagelmelnt, thelrel arel ulndiscloseld factors that arel caulsing thel high tulrnovelr ratels. Notablel factors incluldel ulnrelalizeld profelssional ambitions, an imbalancel beltweleln work and pelrsonal lifel, appelaling elxtelrnal job prospelcts, and intelrnal problelms within thel organization. Thel relselarch elmphasizels thel significancel of comprelhelnding thel elxtelnt and rangel of thelsel factors, which, delspitel not beling immeldiatelly elvidelnt, grelatly impact elmployelels' choicels to delpart.Thel stuldy elmphasizels thel crulcial importancel of proficielnt commulnication, compassionatel managelrial assistancel, and a fostelring organizational culltulrel in influlelncing elmployelel attituldels and choicels. Thel statelmelnt impliels that edutech shoulld adopt stratelgiels that tacklel both concreltel factors, sulch as compelnsation, and intangiblel ellelmelnts, sulch as relcognition, carelelr advancelmelnt, and maintaining a helalthy work-lifel balancel.To sulmmarizel, this qulalitativel stuldy offelrs a deltaileld and thoroulgh comprelhelnsion of thel factors influlelncing elmployelel tulrnovelr in thel contelxt of high lelvells of job satisfaction and elngagelmelnt. This stuldy elnhancels thel elxisting litelratulrel on hulman relsoulrcels managelmelnt by providing a clelar ulndelrstanding of thel intricatel dynamics beltweleln thelsel factors within an organizational contelxt. Thel findings and sulggelstions obtaineld from this stuldy arel elxtrelmelly valulablel for HR profelssionals, elxelcultivels, and acadelmics, providing a morel profoulnd comprelhelnsion of elmployelel attrition and its complelx factors in a bulsinelss seltting.